Social and Psychoanalytic Perspectives on the Use of Physical Punishment among Low-Income African-Americans. Issue 1 (1st January 2020) - Adams, C. Jama
ABSTRACT: Physical punishment is commonly used in low-income Africana families. It is perceived as an effective means of exerting immediate obedience within a cultural context where the child and family members are at high risk of being harmed or killed. While research indicates the ineffectiveness of physical punishment, little attention is paid to the toxic stressors that contribute to its use. I explore the ideology and the social circumstances that drive this behavior. I also highlight the paucity of psychoanalytic conceptual thinking about the social polity in general and on issues of race and class in particular. Thoughts on effective psychoanalytically informed interventions are discussed.